Objective understanding of five front-of-pack labels among consumers in Nelson Mandela Bay, South Africa - Hutton, Tracey Ruth; Gresse, Annelie (The South African journal of clinical nutrition, 2022)
This study aimed to assess the objective understanding of five front-of-pack label formats, namely the Reference Intake, Multiple Traffic Light label, Nutri-Score, health endorsement logo and warning label, among consumers in Nelson Mandela Bay, South Africa. This was a cross-sectional, exploratory study. Interviewer-administered surveys were conducted at 12 randomly selected food retail outlets in an urban setting. A total of 359 adult participants were included in this study. Objective understanding was measured by asking participants to rank food products according to their nutritional quality, using the displayed front-of-pack label. The type of front-of-pack label significantly influenced ranking ability (p < 0.00001). All the evaluative front-of-pack labels significantly improved the participants' ability to identify healthier food products compared with the no-label control. The reductive Reference Intake, however, showed no significant impact on consumer understanding. Evaluative front-of-pack labels significantly improved the participants' ability to identify healthier food products, when compared with the Reference Intake and no-label control. Future research should test the objective understanding of culturally diverse groups in South Africa, particularly among rural populations.